2001
DOI: 10.1002/1521-3765(20010903)7:17<3824::aid-chem3824>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Vancomycin Dimers with Potent Activity against Vancomycin-Resistant Bacteria: Target-Accelerated Combinatorial Synthesis

Abstract: Based on the notion that dimerization and/or variation of amino acid 1 of vancomycin could potentially enhance biological activity, a series of synthetic and chemical biology studies were undertaken in order to discover potent antibacterial agents. Herein we describe two ligation methods (disulfide formation and olefin metathesis) for dimerizing vancomycin derivatives and applications of target-accelerated combinatorial synthesis (e.g. combinatorial synthesis in the presence of vancomycin's target Ac2-L-Lys-D-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
1
8

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 139 publications
(103 citation statements)
references
References 84 publications
0
94
1
8
Order By: Relevance
“…The synthesized headto-head covalent dimer of vancomycin (V D ) is included to assess the effect of dimerization on biological activity. [8] Two glycopeptides with damaged or inactive binding pockets were chosen for comparison with active glycopeptides: a formaldehyde-modified derivative of vancomycin (V*) containing a ring-closed imidazolidinone at the N-terminus, [25] and CDP-I, a biologically inactive degradation product of vancomycin [26] resulting from an unusual aspartic-to-isoaspartic rearrangement at the third residue.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesized headto-head covalent dimer of vancomycin (V D ) is included to assess the effect of dimerization on biological activity. [8] Two glycopeptides with damaged or inactive binding pockets were chosen for comparison with active glycopeptides: a formaldehyde-modified derivative of vancomycin (V*) containing a ring-closed imidazolidinone at the N-terminus, [25] and CDP-I, a biologically inactive degradation product of vancomycin [26] resulting from an unusual aspartic-to-isoaspartic rearrangement at the third residue.…”
Section: Resultsmentioning
confidence: 99%
“…Herein we report our early results of the design and simplification of azide-bearing N o -methylcarbamoyl-L-arginine substrate as a smaller analog of macrocyclic peptide natural product 1 and the use of target-guided synthesis (TGS) (for reports of TGS, see Rideout, 14 Rideout, 15 Ingelese and Benkovic, 16 Boger et al, 17 Maly et al, 18 Nicolaou et al, 19 Greasley et al, 20 Nguyen and Huc, 21 Nicolaou et al, 22 Kehoe et al, 23 Poulin-Kerstein and Dervan, 24 and Hu et al 25 ) for the screening of new and more potent chitinase inhibitors, using the 1,3-dipolar cycloaddition 26 between an azide ligand and a library of acetylenes. The in situ click chemistry for drug discovery is dependent on irreversibly reacting reagents that are inert under physiological conditions, 27 as shown earlier by the discovery of highly potent inhibitors of acetylcholine esterase, [28][29][30][31] carbonic anhydrase II 32 and HIV-1 protease.…”
Section: Introductionmentioning
confidence: 99%
“…25,26,28 Though Van self-associates to form homodimers upon binding to D-Ala-D-Ala, as elucidated by Williams et al, [29][30][31][32][33] this noncovalent dimerization of Van alone is insufficient to act against VRE. Griffin et al, 17,34 Nicolaou et al, 15,16,19,20 and an Eli Lilly group 35 have used organic linkers to synthesize dimers of Van, and demonstrated that covalently linked dimeric Vans exhibit enhanced to potent activity against VRE. It was, however, suggested that the flexibility of the organic linker limited the avidity of the multivalent binding due to the loss of conformational entropy upon binding.…”
Section: Introductionmentioning
confidence: 99%